Ability, inequality and post-pandemic schools : rethinking contemporary myths of meritocracy - Bradbury, Alice (Policy Press, 2021)
Alice Bradbury discusses how the meritocracy myth reinforces educational inequalities and analyses how the recent educational developments of datafication and neuroscience might challenge how we classify and label children as we rebuild a post-pandemic schooling system.